Dynamic studies of refinery sludge gasification in updraft reactor - Ahmed, R. (Trans Tech Publications Ltd, 2014)
Many papers have been published about the gasification of different biomass fuels in fixed bed reactor. To date, no experimental analysis is available in the open literature on gasification of refinery sludge. Therefore the descriptions of dynamic temperature in an updraft reactor for a dry refinery sludge gasification are investigated in details. The rate of the temperature change with operation time and the temperature profiles inside the reactor are taken for various equivalent ratios. The dynamic results show that increasing the ER from 0.195 to 0.244 shift the combustion zone peak temperature from 858°C to 986°C and cause turbulence behavior in reduction zone temperature. With an ER of 0.195, the rate change of temperatures zones was found to be in the ± 50°C min-1 indicating stable gasification process. The axial temperature for starting of a steady state gasification process was found to be between 20 to 60 min operation time in process. © 2014 Trans Tech Publications, Switzerland.